2001
DOI: 10.1016/s0022-5347(05)65712-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Endoscopic Subureteral Polydimethylsiloxane Injection for Treatment of Vesicoureteral Reflux in Children: A North American Clinical Report

Abstract: Endoscopic subureteral polydimethylsiloxane injection is an effective treatment of vesicoureteral reflux in children. The procedure is safe with low associated morbidity. The presence of the polydimethylsiloxane implant can be documented accurately by ultrasound, and there is a strong correlation between implant stability and correction of reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 24 publications
3
40
0
9
Order By: Relevance
“…The use of polydimethylsiloxane has been previously reported with a cure rate of 70-90% in children with VUR [11,12] . In a study of women, the subureteral injection of polydimethylsiloxane corrected the reflux in 37 of 43 ureters (86%) and the mean amount of polydimethylsiloxane was 1.5 ml [13] .…”
Section: Discussionmentioning
confidence: 99%
“…The use of polydimethylsiloxane has been previously reported with a cure rate of 70-90% in children with VUR [11,12] . In a study of women, the subureteral injection of polydimethylsiloxane corrected the reflux in 37 of 43 ureters (86%) and the mean amount of polydimethylsiloxane was 1.5 ml [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Herz et al have shown an overall success rate of 81% after a single injection at an average followup of 18 months. 22 A review reported an overall success rate at one year, two years', and nine years' followup of 86-93%, 80-92%, and 77-100% respectively. 23 However, a specific gun for the injection of PDMS is needed to ensure high pressure during injection and it is technically more difficult to inject.…”
Section: Bulking Agentsmentioning
confidence: 99%
“…These endoscopic procedures are attractive because they are minimally invasive and it is anticipated that they will decrease patient discomfort, surgery extent, and operating time. [1][2][3][4][5][6] Several injectable bulking agents, such as polytetrafluoroethylene (PTFE) paste, 7,8 collagen gel, 9 -12 liquid or particulated silicone, [13][14][15][16] polymethylmethacrylate (PMMA) microspheres, [17][18][19] and autologous fat, 20,21 have been developed and applied in the injection therapies. However, concerns regarding the side effects of these materials have limited general acceptance of their usage.…”
Section: Introductionmentioning
confidence: 99%